Beyond Corporate Social Responsibility: Corporate Sustainability-A Long Terin Perspective - Mehta, Jyotsna Diwan (Gyan Management Journal, 2009)
Issues of social responsibility and ethics are a perennial source of controversy. Several questions require to be answered: How important is it for organi<:,ations to balance social objectives with economic ones? How exactly should a corporate manager think through an ethical issue? What factors should he considered? These are some ofthe important issues that this paper attempts to address. The paper suggests that in order to achieve corporate sustainability organizations must combine the external manifestation of corporate social responsibility along with the internal commitment to ethical and socially responsible behaviour and outline how the organfr:.ation can achieve integral CSR.